ORAL CAVITY HYGIENIC CONDITION IN PATIENTS WITH GENERAL PARODONTITIS AND OPIOID ADDICTION - O.V. Patalakha; I.V. Loskutova (Ukrainian Medical Stomatological Academy, 2016)
Drug addiction is a very actual problem not only in social but also in medical aspects. The results of our studies show that people who suffer from opioid addiction develop not only very heavy changes in their internal organs but also visible changes in their dental maxillary system, particularly general parodontitis develops. (G.P.) In G.P. pathogenesis the barrier function impairment is very important on the background of decreased or even overlapped immunologic reactivity of the organism which results from exogenous factors, parodontal microflora particularly. The aim of our research was to study oral cavity mucous membrane cytokines profile changes. 84 patients with generalized II degree parodontitis were males (65.5 per cent). Family history data revealed opioid addiction which lasted from 2 to 8 years (according to narcological data). Oral cavity hygienic condition was evaluated by means of Fyodorov-Volodkin index. Interleykin (IL-1β, IL-2, IL-4) and TNFα contents in stomatopharynx secretion was revealed by means of imunoenzymatic analysis. The investigation resulted in revealing hygienic index increase which illustrates oral cavity hygienic condition worsening in patients with G.P. and opioid addiction. In most patients (60.7 per cent) with G.P. on the background of opioid addition the hygienic oral cavity condition was characterized as bad (2.6-3.4 scores) and very bad (over 3.5 scores). For 10.7 per cent of the investigated patient the hygienic condition was satisfying (GI up to 2.0 scores) and in 27.4 per cent in the oral hygienic condition was unsatisfactory (GI up to 2.5 scores). The investigation of cytokines degree in stomato-larynx secretion (SLS) in patients with GP with opioid addiction revealed differences in the studied indices depending on the oral cavity hygienic condition. The highest contents of proinflammatory (TNFα, ІL-1β та IL-2) cytokines in SLS was noticed in drug-addicts with GP and with very bad oral cavity hygienic condition (GI over 3.5 scores): TNFα increased 10.05 times (normal (5,6±0,35) pg/ml; Р<0,001); the contents of IL-2-1β - increased 8.93 times (normal (8,2±0,6) pg/ml; Р<0,001) and the contents of IL-2 - 4.81 times (normal (10,2±0,6) pg/ml; Р<0,001). The level of TNFα of SHC of the patients with high hygienic index (HI) (2.6-3.4 scores) increased 6.04 times, IL-1β - 5.63 times, IL-2 - 2.17 times. Number of patients with low HI (2.1-2.5 scores) TNFα concentration increased in 3.29 times, IL-1β - 3.46 times, IL - 2.42 times. Proinflammatory cytokines minimal increase in SHC patients with opioid addiction was revealed in patients with satisfactory oral condition: TNFα and IL-1β were twice as high as the referent norm, IL-2 - 1.28 times higher. The highest level of antiinflammatory cytokine IL-4 in SHC was observed in patients with unsatisfactory state of oral cavity and in the average reached (2,3±0,2 pg/ml), (normal (1,2±0,3) pg/ml) while the minimal cytokine contents was in patients with bad hygienic oral cavity condition (1,1±0,5) pg/ml. In case of satisfactory or bad hygienic oral cavity condition the level of IL-4 with relation to referent form increased 1.5 times and 1.33 times correspondingly. Patients with satisfying hygienic state IL2/IL4 index decreased slowly (7,2±0,5, normal 8,5±0,7). When the GI increased (the oral cavity hygiene became worse) IL-2/IL-4 increased too: in case of unsatisfactory condition - up to 10.7± 0.9, in case of bad condition up to 20.1±1.2 and in case of very bad condition up to 43.2±2.6. Thus, for patients with GP with opioid addiction inflammatory mediators prevail on the background of insufficient antiinflammatory cytokines activity. Oral cavity hygienic condition and stomatopharynx secretion cytokine profile have been investigated in patients with generalized paradontitis and opioid addiction. These investigations resulted in defining hygienic index increase (from 2 to 5,0) which illustrates oral cavity hygienic condition worsening in patients with generalized paradontitis and opioid addiction. The investigated patients revealed high level of proinflammatary cytokines (IL- 1β, TNFα) in mixed saliva which certified stimulizing infectious agent presence in the organism. In stomatopharynx secretion we revealed the growth of inflammation mediators (TNFα, IL-1β) on the background of relative proinflammatory (IL-4) cytokine insufficiency. A positive correlation between the integral index IL2/IL4 and the hygienic index has been revealed in the investigated patients. The results obtained possible use in the process of treatment of patients with general paradontitis with the opioid addiction.